Ethylation of poly(dC-dG).poly(dC-dG) by ethyl methanesulfonate stimulates the activity of mammalian DNA methyltransferase in vitro. - Farrance, I K (1985)
Ethylation of poly(dC-dG).poly(dC-dG) with ethyl methanesulfonate (EtMes), a known carcinogen, at increasing molar ratios of EtMes/C X G base pairs progressively stimulated the methyl-accepting ability of the DNA during in vitro methylation by partially purified rat DNA (cytosine-5)-methyltransferase (EC 2.1.1.37). Maximum stimulation was 2-fold over mock-treated DNA when 2.7% of the guanines were modified at the N-7 position, the major site of ethylation by EtMes in DNA. If a CpG site "hemiethylated" at guanine N-7 mimics a hemimethylated CpG site, we calculate that the enzyme has a relative affinity for hemiethylated CpG 18-fold above unmodified CpG. If ethylation of a dioxyphosphate oxygen of the phosphodiester bond is responsible for stimulation, the relative affinity could be much higher, up to 370-fold.